Study on Flood Optimal Operation of Reservoir based on SA-FOA - Liu, Youchun; Bai, Xiaopeng; Dong, Yafei; Wang, Han; Diao, Yanfang (2021 International Conference on Artificial Intelligence and Electromechanical Automation (AIEA), 2021)
On the basis of considering the flood control safety of the reservoir and protection area, a multi-objective flood optimal operation model of reservoir is established, and a combined algorithm called SA-FOA combined with Simulated Annealing Algorithm(SA) and Fruit Fly Optimization Algorithm(FOA) is used to solve the model. The SA-FOA overcomes the shortcomings of fast convergence speed and easy to fall into local optimal solution of FOA. Taking the flood hydrograph 19630717 and 19640912 of Tianzhuang Reservoir as an example, discharges calculated by SA-FOA are compared with measured values. The results show that the maximum discharges and maximum water levels of the two flood hydrographs calculated by SA-FOA are smaller than those of the measured values, and the discharges calculated by SA-FOA are more uniform, which verifies the safety and feasibility of this algorithm.